POLA KEMITRAAN ANTARA PERUSAHAAN MODAL VENTURA DENGAN USAHA MIKRO KECIL DAN MENENGAH UNTUK MENINGKATKAN DAYA SAING USAHA - Fadhilah, Meita (Yustitia, 2023)
The government's efforts to overcome the difficulties of micro, small and medium enterprises (MSMEs) regarding funding have collided with collateral problems (the banking sector), namely with financing institutions. Financing institutions are believed to be one way to overcome the problems of companies that do not have sufficient assets as collateral for the proposed bank loans. One of the financing institutions that are friends of small entrepreneurs is venture capital or Venture Capital. In general, venture capital financing does not look at collateral belonging to the Business Partner Company. Therefore, Venture Capital Companies are also called long-term investments with the main objective and as compensation for the high risk of the investment is the acquisition of profit, not interest or dividend income